Roy Andrew Miller, Origins of the Japanese language; lectures in Japan during the academic year 1977-78, Publications on Asia of the School of International Studies, Number 34, University of Washington Press, Seattle and London, 1980, xiv + 217 pp., 3 mapas. - Thomas C. Smith Stark (El Colegio de México, A.C., 1986)
-